PERAN PENDIDIKAN EKONOMI DALAM MEMBENTUK GENERASI EKONOMI YANG BERKELANJUTAN - Muhammad Juwantho Lewa; Wahyu Muh. Syata; Yuniyarti Ahiri; Gjoshpink Putra Umar Sakka; Harjun Harjun; Ilhamurrrahan M Hubaib (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
ABSTRACT This study analyzes the role of economic education in shaping a sustainability-oriented generation and formulates strategies for its strengthening in the modern era. The study is motivated by increasing economic inequality, environmental degradation, and the low level of economic and financial literacy among young generations. This research employed a literature review method examining 22 relevant sources published between 2021 and 2026, including indexed journal articles and academic books related to economic education, financial literacy, business ethics, and sustainable development. The analysis was conducted using a thematic synthesis approach through stages of identification, categorization, critical evaluation, and conceptual pattern development. The findings reveal three main patterns. First, the integration of financial literacy and sustainability values into the curriculum significantly contributes to improving responsible economic decision-making skills. Second, contextual and problem-based learning approaches are more effective in fostering awareness of social and environmental impacts than purely theoretical instruction. Third, strengthening business ethics at the secondary education level serves as a key factor in developing long-term sustainable economic orientation. These findings emphasize that adaptive, integrative, and value-oriented economic education should be prioritized within the curriculum as a foundation for sustainable development. ABSTRAK Penelitian ini menganalisis peran pendidikan ekonomi dalam membentuk generasi berorientasi keberlanjutan serta merumuskan strategi penguatannya di era modern. Kajian ini dilatarbelakangi oleh meningkatnya ketimpangan ekonomi, degradasi lingkungan, serta rendahnya literasi ekonomi dan keuangan generasi muda. Penelitian menggunakan metode studi literatur terhadap 22 sumber relevan yang terbit dalam rentang 2021–2026, meliputi artikel jurnal terindeks dan buku akademik terkait pendidikan ekonomi, literasi keuangan, etika bisnis, dan pembangunan berkelanjutan. Analisis dilakukan melalui pendekatan sintesis tematik dengan tahap identifikasi, kategorisasi, evaluasi kritis, dan penarikan pola konseptual. Hasil kajian menunjukkan tiga pola utama. Pertama, integrasi literasi keuangan dan nilai keberlanjutan dalam kurikulum berkontribusi signifikan terhadap peningkatan kemampuan pengambilan keputusan ekonomi yang bertanggung jawab. Kedua, pendekatan pembelajaran kontekstual dan berbasis masalah lebih efektif dalam menumbuhkan kesadaran dampak sosial dan lingkungan dibandingkan pendekatan teoritis semata. Ketiga, penguatan etika bisnis sejak jenjang pendidikan menengah menjadi faktor kunci dalam membangun orientasi ekonomi jangka panjang yang berkelanjutan. Temuan ini menegaskan bahwa pendidikan ekonomi yang adaptif, integratif, dan berbasis nilai perlu diprioritaskan dalam kurikulum sebagai fondasi pembangunan berkelanjutan.